Analysis on aspects of traditional (‘indigenous’) and western thinking in the classical and modern Burmese elites’ discourse concerning madness. - Myint Zan, (Universiti Kebangsaan Malaysia, 2010)
English translations of excerpts from a translated traditional medical text in Burmese on what it termed the ‘madness disease’ is provided and commented on. It is asserted that the text confuses between causes, symptoms, etiology and treatment of mental disorders. As to the nature of ‘the cause’ of ‘madness disease’ the text gives the most emphasis on the supernatural, esoteric or ‘macabre’ causes of madness that is considered as an ‘affliction’ when the subject is ‘seized’ or possessed by the ‘nats’ roughly translated as evil ‘spirits’ or the agents of the evil spirits. The Burmese translation of this text which was published around the year 1963 directly contradicts the educative books on psychiatry written by a Burmese psychiatrist and a literary writer which was published in the same decade and which in effect ‘debunks’ the notion of madness being caused by the nats. In contrast to those discoursed in the traditional texts, the modern Burmese elites inclusive of psychiatrists, psychologists and literary writers adhere to and directly or indirectly espouse the tenets of the modern, Western concepts of mental illness. The theories of Michel Foucault and Thomas Szasz on mental illness can be considered as challenges to or strong dissents from the ‘main stream’ Western concepts of mental illness. The article concludes with an analysis of the possible causes of the lack of interest, discussion and discourse among even a handful of Burmese elites on the ‘dissident’ theories of Foucault and Szasz on the subject.